2020
DOI: 10.1590/s1678-3921.pab2020.v55.01279
|View full text |Cite
|
Sign up to set email alerts
|

Farm systems, soil chemical properties, and clay dispersion in watershed áreas

Abstract: The objective of this work was to evaluate the effect of different farm systems on clay dispersion and its relationship with soil chemical properties and the no-tillage system participatory quality index (IQP), in watershed areas in the west of the state of Paraná, Brazil. The farm systems evaluated were: no-tillage; no-tillage with crop succession; no-tillage with soil disturbance; and conventional system. In addition, the farm systems were evaluated for their IQP. Soil samples were collected at 0.0-0.20-m so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…When classifying the farms as NT or NTS (Table 4), we noted that only two cases (5.4 %) were classified as NTS, agreeing with the three principles simultaneously, while the rest did not meet one or more principles. Nunes et al (2020a) found 10.3 % of NTS among farms evaluated by the PQI methodology in western Paraná, a percentage higher than that in this study. Thus, the adoption of NTS in this study is limited to 5 % of farms, which corroborates the estimate that most of the area in use in Brazil is NT and not NTS.…”
Section: Case Study 2: Nts Participatory Quality Indexcontrasting
confidence: 88%
See 1 more Smart Citation
“…When classifying the farms as NT or NTS (Table 4), we noted that only two cases (5.4 %) were classified as NTS, agreeing with the three principles simultaneously, while the rest did not meet one or more principles. Nunes et al (2020a) found 10.3 % of NTS among farms evaluated by the PQI methodology in western Paraná, a percentage higher than that in this study. Thus, the adoption of NTS in this study is limited to 5 % of farms, which corroborates the estimate that most of the area in use in Brazil is NT and not NTS.…”
Section: Case Study 2: Nts Participatory Quality Indexcontrasting
confidence: 88%
“…These indicators are crop rotation intensity (RI), crop rotation diversity (RD), persistence of straw (PS), soil tillage frequency (TF), correct terracing (CT), soil conservation evaluation (SC), balanced soil fertilization (BF), and adoption time (AT), for which ideal situations are known to promote soil quality over time (Itaipu Binacional and Febrapdp, 2011;Rollof et al, 2011a). It is worth noting that the three pillars of the NTS are included in the IQP by the RD, PS, and TF indicators for crop rotation, permanent soil cover, and minimum soil disturbance (Nunes et al, 2020a), but the methodology is not restricted only to these and evaluates a set of conservation practices. 2 0 1 2 / 2 0 1 3 2 0 2 0 / 2 0 2 1 2 0 0 0 / 2 0 0 1 2 0 0 1 / 2 0 0 2 2 0 0 2 / 2 0 0 3 2 0 0 3 / 2 0 0 4 2 0 0 4 / 2 0 0 5 2 0 0 5 / 2 0 0 6 2 0 0 6 / 2 0 0 7 2 0 0 7 / 2 0 0 8 2 0 0 8 / 2 0 0 9 2 0 0 9 / 2 0 1 0 2 0 1 0 / 2 0 1 1 2 0 1 1 / 2 0 1 2 2 0 1 3 / 2 0 1 4 2 0 1 4 / 2 0 1 5 2 0 1 5 / 2 0 1 6 2 0 1 6 / 2 0 1 7 2 0 1 7 / 2 0 1 8 2 0 1 8 / 2 0 1 9 2 0 1 9 / 2 0 2 0 From a structured questionnaire that can be used by farmers, technicians, and extensionists, the information is transformed into quantitative indicators, assigning a score and classification for the NTS quality, as well as indicating the strengths, weaknesses and potential improvements to be made.…”
Section: Case Study 2: Nts Participatory Quality Indexmentioning
confidence: 99%
“…In their study, the management system with the least soil disturbance (continuous no-tillage) exhibited the highest dispersion degree of the clay fraction compared to systems that promoted greater soil tillage, regardless of the agricultural implementation used or the intensity of soil disturbance. However, the negative mechanical effects of soil disturbance on clay fraction dispersion can be partially neutralized by proper soil chemical management and fertilization of the production system, as pointed out by Nunes et al (2020).…”
Section: Effects Of Management Systems and Formation Pathways On Aggr...mentioning
confidence: 99%